Shape Memory Materals Based on a NiMnSb Alloy and Polylactic Acid/Polyhydroxyalkanoate: Evaluation of The Chemical And Physical Properties - Coskun, Meltem; Kok, Mediha; Pekdemir, Mustafa Ersin (Wiley-V C H Verlag Gmbh, 2024)
In this study, NiMnSb alloy and PLA/PHA blend composite films with shape memory properties, which exhibit magnetic, elastic, and smart properties at the same time, were prepared by solution casting method. After the magnetic shape memory alloy (MSMA) used in different ratios was doped into the polymer, its effect on the characteristic functional groups of PLA and PHA was examined by attenuated total reflectance-infrared spectroscopy (ATR-IR). When the thermal data were examined, it was determined that as the NiMnSb ratio increased, the percentage residue amount increased and the highest residue amount at 500 degrees C was in the PLA/PHA blend composite film containing 20 % alloy. In X-ray diffraction (XRD), it was observed that the characteristic signal of the NiMnSb alloy in polymer blend composite films became evident with increasing concentration at 2 theta=45 degrees (222). VSM results showed that when a ferromagnetic material such as NiMnSb was doped into the diamagnetic PLA/PHA blend film, the resulting composite now showed ferromagnetic properties. In addition, it has been determined that MSMA further improves this feature of the PLA/PHA blend, which has a shape memory effect. In this study, composite films were prepared by adding different percentages of NiMnSb shape memory alloy to the PLA/PHA shape memory polymer blend. It was determined that the thermal stability and saturation magnetization values of the composites increased significantly with the increasing percentage of NiMnSb alloy. In addition, it was observed that the polymer blend with shape memory feature maintained this feature with the addition of NiMnSb alloy. image
Keywords: magnetic shape memory alloy; shape memory polymers; composite; blend; magnetic materials